Antioxidant Potential of Solanumkurzii Br. Berry: A Folk Medicinal Food Berry used in Arunachal Pradesh, North- East India (Global Journal of Medical Research, 2014)
Solanumkurzii Br. berry used as folk food medicine among the Adi tribe of Arunachal Pradesh. The methanol extract of berry were evaluated for total phenolic content (Folin-Ciocalteu's method), total flavonoid content (colorimetric method) and antioxidant potential ((DPPH & ABTS). The methanol extract contains considerable contents of phenolic (14.60 mg GAE/g) and flavonoid (89.00 μMRE/g) with antioxidant potential of 30.75 μM/g and 257.74μM/g in ABTS and DPPH assay respectively. The folk use as food and medicine and antioxidant potential of Solanumkurzii berry is discussed in the paper.
Keywords: solanumkurzii; phenolic content; flavonoid content; antioxidant; folk food; indigenous people